If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + -10 = 20 Reorder the terms: -10 + -10x = 20 Solving -10 + -10x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -10x = 20 + 10 Combine like terms: -10 + 10 = 0 0 + -10x = 20 + 10 -10x = 20 + 10 Combine like terms: 20 + 10 = 30 -10x = 30 Divide each side by '-10'. x = -3 Simplifying x = -3
| 0.25-14=26 | | 12x-4(x-4)=32 | | N^2+2= | | 14(x-2)=-9 | | 0.26-14=26 | | (T-8)(2t-1)=0 | | 13(x-4)=91 | | 14v+6(v-2)=38 | | 11g=-55 | | V(8)+9.3=3.5 | | 5(x+2)+10(3+2x)=50 | | 2+j=8 | | 190=106-x | | c/1.5=-2.9 | | (12+x)(5+x)=120 | | 4-r=-3 | | -7x+2(x-6)=-17 | | 4c=68 | | F=7/3(n-65) | | (6x-4)(7x+2)=x | | 14L=42 | | 4K-2k-8= | | 6=-2.4x | | 2x-19-x=-11 | | -8=-6w+4(w-4) | | x^2-x-0.125=0 | | 1x-7=-2x-5 | | 6=-7u+4(u+6) | | -12+7(5)= | | 7f+3G= | | 6y^2-y=5 | | 6y+(2y+5)= |